2013
DOI: 10.3892/ijo.2013.2135
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a 5-fluorouracil-resistant triple-negative breast cancer cell line

Abstract: Triple-negative breast cancers (TNBCs) are defined as tumors that lack expression of estrogen receptor, progesterone receptor and human epidermal growth factor receptor 2. Clinically, TNBC patients are treated with cytotoxic drugs including 5-fluorouracil (5-FU). However, TNBCs develop resistance to such drugs after a series of treatments. To elucidate the mechanisms of drug resistance, establishment of drug-resistant cancer cell lines should be one of the most useful model systems. However, 5-FU-resistant TNB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Next, a proteome analysis was performed using a DiNa-AI nano LC System (KYA Technologies, Tokyo, Japan) coupled with a QSTAR Elite hybrid mass spectrometer (AB Sciex) through a NanoSpray ion source (AB Sciex), as previously described 13) . Briefly, mobile phase A included 98% water (2% acetonitrile [ACN], 0.1% formic acid) and mobile phase B included 70% ACN (0.1% formic acid, 30% water).…”
Section: Measurement Of the Nitrate (No3 ) Levels In The Serummentioning
confidence: 99%
“…Next, a proteome analysis was performed using a DiNa-AI nano LC System (KYA Technologies, Tokyo, Japan) coupled with a QSTAR Elite hybrid mass spectrometer (AB Sciex) through a NanoSpray ion source (AB Sciex), as previously described 13) . Briefly, mobile phase A included 98% water (2% acetonitrile [ACN], 0.1% formic acid) and mobile phase B included 70% ACN (0.1% formic acid, 30% water).…”
Section: Measurement Of the Nitrate (No3 ) Levels In The Serummentioning
confidence: 99%
“…Russo et al showed that certain proteins such as zonulin, glucagon-like peptide-2 (GLP-2), epidermal growth factor (EGF) and ghrelin play a role in the response to FEC in breast cancer cells [4]. Previous studies have shown that the high mortality of breast cancer can be partly attributed to the acquisition of drug resistance during chemotherapy [5], [6]. Despite the steady improvement of 5-FU-basedtreatment regimens, the patient response rate to 5-FU-based chemotherapy remains modest mainly due to the development of drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, 5-FU resistance is caused by an increase in the 5-FU-degrading enzyme dihydropyrimidine dehygrogenase (DPYD) and 5-FU-targeting enzyme thymidylate synthase (TS) [30]. On the other hand, ABC family proteins, such as Multi Drug Reactivity 1 (MDR1), are related to multiple drug resistance in cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The determinants of the resistance mechanisms to 5-FU include the enzymes involved in the 5-FU metabolism pathway [30]. To exert its cytotoxic effects, 5-FU is converted to its active metabolites by several enzymes and the levels of these enzymes have been associated with 5-FU sensitivity [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation